Fetal Anasarca in Himalayan Sheepdog - Mahajan, Mohit; Prasad, Shiv; Singh, Vipin; Arya , Damini (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fetal anasarca (dropsy of fetus) is a congenital anomaly, grossly characterized by an increase in the fetal volume due to excessive fluid build-up under the cutaneous layer (subcutaneous tissue). Particularly the head and hind limbs are involved, with concurrent accumulation within the peritoneal and pleural cavities (Noakes et al.;, 2001). “Congenital edema,” “hydrops fetalis” or “walrus syndrome” are other terms used for fetal anasarca. These pups anatomically resemble hippos and walrus and thus are called water puppies and walrus puppies. As they are more prominent compared to normal pups, they often result in dystocia due to fetal oversize and lead to high infant mortality (Hopper et al., 2004; Monteagudo et al., 2002). Pups affected with fetal anasarca may be one or the complete litter. Anasarca is common in large and small ruminants, but rare cases in small pet animals such as canines and felines (Prabaharan et al., 2016) are reported. Canine breeds predisposition to fetal anasarca is reported in English bulldog, French bulldog, and Pugs. Studies have suggested the use of diuretics such as thiazide as the primary treatment for congenital edema like anasarca in the fetus (Hopper et al., 2004; Hoskins, 2008) with only limited success.